Cabozantinib combination therapy for the treatment of solid tumors: a systematic review. (July 2022) - Castellano, Daniel; Apolo, Andrea B.; Porta, Camillo; Capdevila, Jaume; Viteri, Santiago; Rodriguez-Antona, Cristina; Martin, Lidia; Maroto, Pablo
Background: Cabozantinib monotherapy is approved for the treatment of several types of solid tumors. Investigation into the use of cabozantinib combined with other therapies is increasing. To understand the evidence in this area, we performed a systematic review of cabozantinib combination therapy for the treatment of solid tumors in adults. Methods: This study was designed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses, and the protocol was registered with PROSPERO (CRD42020144680). On 9 October 2020, we searched for clinical trials and observational studies of cabozantinib as part of a combination therapy for solid tumors using Embase, MEDLINE, and Cochrane databases, and by screening relevant congress abstracts. Eligible studies reported clinical or safety outcomes, or biomarker data. Randomized and observational studies with a sample size of fewer than 25 and studies of cabozantinib monotherapy were excluded. For each study, quality was assessed using National Institute for Health and Care Excellence methodology, and the study characteristics were described qualitatively. This study was funded by Ipsen. Results: Of 2421 citations identified, 32 articles were included (6 with results from randomized studies, 24 with results from non-randomized phase I or II studies, and 2 with results from both). The most commonly studied tumor types were metastatic urothelial carcinoma/genitourinary tumors and castration-resistant prostate cancer (CRPC). Findings from randomized studies suggested that cabozantinib combined with other therapies may lead to better progression-free survival than some current standards of care in renal cell carcinoma, CRPC, and non-small-cell lung cancer. The most common adverse events were hypertension, diarrhea, and fatigue. Conclusion: This review demonstrates the promising efficacy outcomes of cabozantinib combined with other therapies, and a safety profile similar to cabozantinib alone. However, the findings are limited by the fact that most of the identified studies were reported as congress abstracts only. More evidence from randomized trials is needed to explore cabozantinib as a combination therapy further.